Accounting balance as a historical category: the contribution of scientists to the halicy of the second half of the XIX- first half of the XX century in the development of balance science - Lemishovska, O. (Видавництво Львівської політехніки, 2020)
The origins and the evolution of the balance sheet in the system of theoretical and conceptual foundations of balance theories are considered. The researches of scientists of Galicia of the second half of XIX – first half of XX century are analyzed. the accounting paradigms they have formed and theoretical developments with a view to their contribution to improving the balance sheet structure. The hypothesis of this study is the assumption that the period of individual ideas for the development of balance science and relevant methodological approaches that can objectively be used as a means of enhancing the validity of contemporary research. The scientific validity of the proposed use of ideas formed in the past in the designated territory is based on the following postulates: proposals for improving the balance sheet at the expense of past experience in the principles of valuation of balance sheet items and the introduction of the methodological principles of capital structuring formulated in the past (balance sheet liability). These approaches are justified in line with contemporary financial management paradigms, including sustainable development management concepts. The scientific novelty of the study is that for the first time in historiography, objective data on the contribution of Galicia's scientists to the global development of balance science are presented, and suggestions have been made as to the possibility of using certain developments to deepen modern principles and approaches to improving the form of balance generalization. The methodology of the study is based on the principles of historicism, scientificity, verification, authoritative objectivity, moderate narrative constructivism. Using general scientific and interdisciplinary methods of cognition, conceptual and methodological developments of Western Ukrainian scientists in the field of balance studies in the period declared by the study were evaluated. Systematic methodology is ensured by the coherent use of general scientific (analysis, synthesis, generalization), historical (historical-genetic, historicalsystem) methods and the application of specific tools for the subject area of knowledge.
Keywords: financial statements; balance sheet; balance theory; asset and liability balance; the theory of balance of the territory of Galicia; conceptual and methodological works of Western Ukrainian scientists; М41; В15; N01; 657.01; 3(091); 330.8(4/9)«18/19»